Whole blood flow cytometry protocol for the assessment of platelet phenotype, function, and cellular interactions. (18th August 2021) - Yaw, Hui Ping; Van Den Helm, Suelyn; Linden, Matthew; Monagle, Paul; Ignjatovic, Vera
Abstract: Platelets are a key component of the hemostatic system and their roles in inflammation via interactions with leukocytes have also gained attention in recent years. Changes in platelet phenotype and function can cause bleeding and/or thrombosis and, as such, monitoring platelet-specific changes is crucial to assessing hemostasis in the clinical setting. Currently, available platelet function tests such as platelet aggregometry and thromboelastography require a large volume of blood, which is a major limitation for the pediatric population. Whole blood flow cytometric analysis of platelets is increasingly utilized in recent years, primarily due to the sensitivity of this method, but also because it only requires a small amount of blood with minimal sample manipulation. We have developed a whole blood flow cytometry methodological approach that enables the assessment of platelet phenotype, function, and their interactions with monocytes and neutrophils.